Asset monitoring procedure in Puteri Island Resort / Muhammad Shahid Muzafar - Muzafar, Muhammad Shahid (Universiti Teknologi MARA, Perak, 2022)
Besides constructing a new building, existing buildings with various uses such as office, restaurant and more, play an important role in the development of a state. Existing buildings are also important to be monitored and maintained, therefore this report will discuss the method used called ‘asset monitoring’. This method is used to ensure all company-owned buildings in good and optimal condition. The objectives of this report are to identify all the procedure of asset monitoring work and problems face in performing this work. The finding from this work is the issue found during performing the monitoring work such as hygiene issues, damage issues and loss issues. In performing this work, there are two methods used to obtain data and information. First, through observation. Observation has been made by visiting the buildings. Second, through interview. In this method, interviewed a person who is experienced in this work, to obtain more detailed information about the procedure. With performing this work, all the company-owned buildings will be maintained and always at an optimal level and can be used in the future without any problems.